HUBUNGAN KEBERSIHAN KULIT WAJAH DENGAN TIMBULNYA AKNE VULGARIS PADA SISWA TATA KECANTIKAN DI KOTA PADANG - Mulya Syabantini Prima (JURNAL PENDIDIKAN DAN KELUARGA, 2018)
Acne usually occurs more often in men than women in their teens, but with increasing age, acne is more common in women. Acne vulgaris is called multifactor, which is caused by many factors including climate, cleanliness, cosmetic use, psychological or fatigue, age, race, food, gender and genetic which can indirectly spur an increase in the process of pathogenesis of acne vulgaris. Hygiene of facial skin is important in supporting the success of cleaning and treating acne vulgaris. The objective of the research to determine the relationship of facial skin hygiene with the emergence of acne vulgaris in Students of Beauty Vocational School in Padang City. This type of research is a descriptive correlational methode. This research was conducted in October 2018 at SMK Negeri 6 and SMK Negeri 7 Padang. The population in this study were students of Beauty Vocational at SMK Negerti 6 and SMK Negeri 7 Padang. Sampling using Slovin formula. Data analysis techniques are using product moment correlation analysis. The results of the analysis show that the average level of facial skin hygiene of SMK students in Padang City 's Beauty System is 83.09 with the most frequency distribution in the good category as many as 46 people (60.5%). The average incidence of facial skin acne vulgaris students of the Vocational School of Beauty in Padang City obtained an average value with the most frequency distribution in the light category as many as 51 people (67.1%). There is a significant negative correlation between facial skin hygiene and the emergence of student acne vulgaris (r= - 0.407 and t= 3.83).